PENINGKATAN KEMAMPUAN MEMBACA PUISI MENGGUNAKAN PEMODELAN DI SEKOLAH DASAR - Herlina, Herlina; Rosnita, Rosnita; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is for increase ability student read. Poetry with use modeling on student in class III school basic contry 21 Rantau Sibaju district Bengkayang. This research use approach qualitative, method that used descriptive with form research action class (RAC) and is collaborative. The place research held in school basic contry 21 Rantau Sibaju City Singkawang class III that number22 student with subject research teacher and student class III. Teachnique data collector that used that is teachnique observation and teachnique scrutiny document with tool. Collector data that is instrument sheet assessment ability teacher plan learning, instrument sheet asessment ability teacher doing learning and document results learning student in the form of sheet asessment read poetry. The research do for 2 cycle with 2 meeting on every the cycle. Asessment resuts planning, implementation, learning from cycle i 3,00 and 3,08 increase as big as 0,08 and cycle II that is 3,50 and 3,80 increase as big as 0,3. Asessment results implementation learning from cycle I 3,00 and 3,18 increace as big as 0,18 and cycle II that is 3,45 and 3,72 increase as big as 0,27. Asessment results read poetry from cycle I that is 62,63% only there is 10 person that complete while on cycle II 74,24% only stay 2 student that no complete. Based on data that obtained could concluded happen enhancement on every cycle. With thereby, research use modelling with read poetry class III school basic country 21 Rantau Sibaju Kabupaten Bengkayang could increase skill student read poetry. Keywords: Enhancement, Read Poetry , Learning Contexstual Component Modeling.